2011
DOI: 10.1007/s12975-011-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Stem Cell Transplantation for Stroke

Abstract: Stroke is the third leading cause of death and the leading cause of adult disability in North America. Emphasis has been placed on developing treatments that reduce the devastating long-term impacts of this disease, and preclinical research on stem cell therapy has demonstrated promising results. However, questions about the optimal cell delivery method and timing of cell transplantation are not fully answered. Recent findings suggest that intravascular stem cell delivery is a safe and efficacious alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…The main reason for this is that cells bypass filtering organs, such as the lung, the spleen, and the liver 3 . Pre-clinical studies have also demonstrated that targeted delivery to the ischemic brain has well-defined molecular mechanisms, attracting cells from the intravascular to the intraparenchymal space 4 . Cell-sorting or cell engineering to improve the targeted delivery needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this is that cells bypass filtering organs, such as the lung, the spleen, and the liver 3 . Pre-clinical studies have also demonstrated that targeted delivery to the ischemic brain has well-defined molecular mechanisms, attracting cells from the intravascular to the intraparenchymal space 4 . Cell-sorting or cell engineering to improve the targeted delivery needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell transplantation into the adult central nervous system (CNS) as cellular therapy has been suggested for treatment of neurodegenerative diseases such as Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS), CNS trauma disorders such as spinal cord injury (SCI) and traumatic brain and axonal injury, as well as stroke and brain tumors (1,5,17,30,33,45,47,48,51). In animal models of traumatic brain injury (TBI), recent studies have demonstrated transplantation of several types of stem cells for potential therapy, and stem cell-based therapies are being evaluated for safety and efficacy in humans (ClinicalTrials.gov Identifier: NCT02028104).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of intravascular neural stem cell (NSC) transplantation, our lab has shown a direct correlation between the number of cells surviving in the brain after intra-arterial (IA) transplantation and positive functional outcomes (13). However, intravascular transplantation of human NSCs into rodents has often demonstrated a very low rate of cell engraftment (5). Therefore, we sought a way to improve cell engraftment following transplantation in the hopes of improving functional outcomes after stroke.…”
Section: Introductionmentioning
confidence: 99%